The Srikandi Application: Implementation of the Srikandi Application in Achieving Archival Digitization Within Local Government - Putri Melia Amaryanti; Sri Wulandari (PT Publikasiku Academic Solution, 2026)
This paper discusses the application of SRIKANDI in facilitating the process of digitization of the archives in the Cirebon Regency Social Affairs Office. The study is qualitative in nature, and the methods of data collection include observation, interviews, and documents. The policy implementation analysis is based on the theory of G. Shabbir Cheema and Dennis A. Rondinelli, which focuses on environmental conditions, inter-organizational relationships, organizational resources, and the nature and ability of implementers. The results of the research indicate that the application of the SRIKANDI application is not yet optimal, as evidenced by the prevalence of traditional work culture, the lack of human resource competencies, and the insufficient motivation among employees to use the digital system. Although there is policy support and technological infrastructure, these have not been fully utilized. The Cirebon Regency Social Services Agency has undertaken several improvement activities, including training, internal coordination, and upgrading of infrastructure. This research focuses on maximizing the adoption of the SRIKANDI application by enhancing the capacity of officials and fostering a sustainable transformation of the work culture.